Initial-Boundary Value Problems for Local Fractional Laplace Equation Arising in Fractal Electrostatics - Yang, Xiao-Jun; Srivastava, H. M.; Baleanu, Dumitru (Journal of Applied Nonlinear Dynamics, 2026)
The initial-boundary value problems for the local fractional Laplace equation, which arises in fractal electrostatics, are investigated in this article. The non-differentiable solutions with different initial and boundary conditions are obtained by using the local fractional series expansion method.